Pricing Vulnerable Options Using Conditional Expectation Transform Methods - Han Wang (Discrete Dynamics in Nature and Society)
In this study, a conditional expectation transform (CET) method was developed for solving high-dimensional systems arising in vulnerable options pricing. The CET was formulated to recast the pricing of vulnerable options into that of exchange-traded options under special terminal condition. Then, traditional option pricing methods are deployed to price the exchange-traded options, and an analytical formula for vulnerable options is obtained. The vulnerable European option, vulnerable Barrier option, and vulnerable floating Lookback option were analyzed as examples to demonstrate the effectiveness and accuracy of the CET method. Numerical examples were provided to confirm the theoretical results.